O-OGC05 Every veneSection Counts – can we improve patient experience in high-risk upper gastointestinal surgery patients?. (16th December 2021) - Bentley, Richard; Ireland, Edward; Griffiths, Nathan; Beharall, Bethan; Paul, Barry; Pennington, Jane de; Browell, Christopher
Abstract: Background: Patients with upper gastrointestinal (UGI) malignancy undergo major surgical resections resulting in significant postoperative inpatient stays. Central venous access is utilised to aid management of intraoperative physiology, immediate post-operative care and perioperative complications, which are often complex. Central venous catheters (CVC) and peripheral intravenous (IV) cannulae have a relatively short safe duration; consequently these patients undergo numerous unpleasant venous access attempts. Our aim was to optimise quality of care and patient satisfaction in this high-risk patient group, by inserting Peripherally Inserted Central Catheters (PICCs) pre-operatively to facilitate administration of intravenous (IV) medications, fluids and perioperative blood sampling. Methods: We reviewed venous access management in this group from October 2019 to May 2020;recording numbers of IV cannuale, CVCs and any associated complications. From September 2020, all patients deemed high-risk, undergoing a major UGI resection were offered a PICC, inserted pre-operatively. We recorded data on use of CVCs and alternative venous access devices, peripheral venous stabs, complications and overall patient experience. Results: Over the first 6 month period we sited 30 PICCs - significantly fewer patients required a perioperative CVC (9% vs 64%) in the PICC group and these lines remained in situ for much longer than CVCs (mean 17 days vs 4.7 days). The PICC group required fewer peripheral cannulae (mean 2.73 vs 5.95 per patient). One patient suffered deep vein thrombosis (DVT) but there were no other adverse consequences. Two patients (9%) were treated for fast ventricular response to Atrial Fibrillation successfully on their surgical ward, with IV Amiodarone via their PICC, negating need for critical care admission. Patients in the baseline study required peripheral stabs for blood sampling most days of their inpatient stay (median 12.5 days), whereas the majority of samples were taken from PICCs in the post-intervention group. Satisfaction scores were high in 100% of cases. Conclusions: The introduction of PICCs in our high-risk UGI patients has been a huge success, positively influencing the patient journey. There are demonstrable outcome benefits with reduction in CVCs, peripheral cannulations and phlebotomy attempts. In addition, it has facilitated easier and timelier perioperative administration of IV fluids and medication, optimising patients' experiences and care.